Mongolia : Improving Public Investments to Meet the Challenge of Scaling Up Infrastructure - World Bank (Washington, DC, 2013)
The objective of this report is to analyze in depth the current public investment management system and to assess whether or not it is able to meet this challenge of delivering good quality projects in the priority areas in a macro-economically sustainable manner; and to recommend what needs to be done to improve the system so that it is able to effectively transform natural resource revenues into sustainable capital assets. In making its recommendations, this report focuses on some of the details that need to be laid out in implementing regulations in order to make the Fiscal Stability Law (FSL), Budget Law of Mongolia (IBL), and Public Procurement Law of Mongolia (PPLM) work. The report also suggests amendments to some of the existing laws that pose a risk to meeting the four objectives. In proposing policy options, the report is conscious of the political economy of reform and, wherever possible, analyzes the compatibility of the technical solutions with the political interests of policy-makers.